2005
DOI: 10.1111/j.1460-2695.2005.00917.x
|View full text |Cite
|
Sign up to set email alerts
|

J‐integral analysis of cord‐rubber serpentine belt using neural‐network‐based material modelling

Abstract: A B S T R A C T A known factor that limits the performance of automotive front-end accessory serpentine belt drive is cracking of the elastomer located in the rib tip. In this paper, fracture experiments were conducted using single-edge notched tension (SENT) specimens to study the fracture behaviour of a belt rib compound. A finite-element modelling method utilizing singular elements for crack in rubber solid was proposed and implemented in both planestress and 3D solid models using ABAQUS. A newly developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…This is because of the increase in load distribution at the crack tip. This phenomenon is in conformance to the findings in Song et al [4]. rise to larger displacements at the boundaries of the local model, thereby resulting in larger crack opening at the rib tip, and thus a larger value of the J-integral.…”
Section: Effect Of Pulley Load On J-integralsupporting
confidence: 87%
See 1 more Smart Citation
“…This is because of the increase in load distribution at the crack tip. This phenomenon is in conformance to the findings in Song et al [4]. rise to larger displacements at the boundaries of the local model, thereby resulting in larger crack opening at the rib tip, and thus a larger value of the J-integral.…”
Section: Effect Of Pulley Load On J-integralsupporting
confidence: 87%
“…The temperature effects on stresses, strains, and belt-pulley contact slip rates were studied in detail. In another study, Song et al [4] reported a neural network based rubber material model to evaluate the J-integrals for different crack lengths. The results were compared with analytical and experimental findings.…”
Section: Introductionmentioning
confidence: 98%
“…Song studied the fracture characteristics of reinforced tip elastomer [5] of transmission belt, the relationship between the crack length, load size and the J integral value. ABAQUS software was used to simulate local structural fracture crack characteristics and transmission rubber material with the characteristics so as to provide a theoretical reference for the belt life prediction.…”
Section: Crack Propagation Methodsmentioning
confidence: 99%
“…The merit of the method is that it can approximate the test data much more accurately than any available model. Song et al [14,15] verified the accuracy of this model through analysis of cord-rubber serpentine belt. This methodology, hence, is adopted in the present study to derive the hyperelastic constitutive material law for rubber compound used in ABAQUS/Explicit algorithm.…”
Section: Introductionmentioning
confidence: 93%